Fostering MahÄrah KitÄbah through Picture-Based Controlled Writing with AI-Generated Visual Stimuli - Nandatasia, Riqqa Aurelia; Nugrahawan, Ahmad Rizki (Alibbaa’: Jurnal Pendidikan Bahasa Arab, 2026)
Although visual-based approaches have been applied in Arabic writing instruction, their integration with controlled writing remains underexplored. This study examines the effectiveness of Picture-Based Controlled Writing in improving Arabic writing skills, known as mahÄrah kitÄbah, among tenth-grade students at MA Al-Falah Klender. Using a quantitative quasi-experimental design, 22 students were divided into experimental and control classes. The treatment combined sequenced visual stimuli with controlled writing tasks through guided sentence completion to help students organize ideas and use Arabic grammatical structures more accurately. To strengthen the quality and consistency of learning resources, generative AI was employed to create the visual stimuli and selected sentence prompts used in instructional materials as well as the pre-test and post-test. The experimental class showed a moderate learning gain with an N-Gain value of 0.53, suggesting the potential of the Picture-Based Controlled Writing approach in supporting Arabic writing development.